Non-standard work: What's it worth? Comparing alternative measures of workers' marginal willingness to pay - Andrea Geraci; Mark L. Bryan (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We compare two alternative ways of measuring workers' marginal willingness to pay (MWP) for four non-standard working arrangements: flexitime, part-time, night work, and rotating shifts. The first method is based on job-to-job transitions within a job search framework, while the second is based on estimating the determinants of subjective well-being. Using BHPS panel data from 1991-2008, we relate differences in the results to conceptual differences between utility and subjective wellbeing proposed recently in the happiness literature. We conclude that there is not a single representation of MWP: utility trade-offs (revealed by choices) need not be the same as wellbeing trade-offs; and we find evidence that subjective wellbeing is traded off against other goods that provide utility. Overall, we find that workers care particularly about their number of weekly hours.
Keywords: J28; J30; J32; J60; 330; Willingness to Pay; Non-standard work; Job Satisfaction; Subjective Well-Being; Job Duration